Fresno County Bar Association-Witkin Luncheon - Watkins, Howard::::::::: (1983)
Fresno County Bar Association President Elect Rodney Worrel, Bernard Witkin, Robert Oliver speaking at lectern, Fresno County Bar Association Doug Jensen